Megachange : the world in 2050 - Franklin, Daniel. (ed.); Andrews, John (ed.) (London, 2012)
In 2050 there will be 9.3 billion people alive - compared with 7 billion today - and the number will still be rising. The population aged over sixty-five will have more than doubled, to more than 16 per cent; China's GDP will be 80 per cent more than America's; and the number of cars on India's roads will have increased by 3,880 per cent. And, in 2050 it should be clear whether we are alone in the universe. What other megachanges can we expect - and what will their impact be? This comprehensive and compelling book will cover the most significant trends that are shaping the coming decades, with each of its twenty chapters elegantly and authoritatively outlined by Economist contributors, and rich in supporting facts and figures. It will chart the rise and fall of fertility rates across continents; how energy resources will change in light of new technology, and how different nations will deal with major developments in science and warfare. Megachange is essential reading for anyone who wants to know what the next four decades hold in store.
Keywords: Development and change